Emotional Intelligence as A Psychological Category (Diversity Research: Journal of Analysis and Trends, 2023)
in this article various approaches and judgments to the definition of emotional intelligence as a psychological category are considered. This phenomenon causes a large number of disputes and disagreements among the authors, therefore the article contains various opinions and classifications, which to some extent complement each other. The main similarities between emotional and social intelligence, as well as the criteria by which these concepts are distinguished, are considered. The evolution of views on the nature and specificity of emotional intelligence, interaction of emotional and intellectual development of the personality is presented. Ideas about the structure of emotional intelligence are analyzed, the main features of each intellect model are determined, their criteria and parameters are considered. The authors singled out common patterns for all approaches in the study of emotional intelligence, as well as the specifics of each of the above approaches. The use of an integrative approach in the study of the emotional and intellectual development of the individual is justified. The authors points out that emotional intelligence acts as a determining factor in the socialization and development of the personality, determines the various methods of studying it, shows its place in the structure of social intelligence, analyzes the role of information in the formation of emotional intelligence